Preparação de metabólitos humanos do montelucaste através da bioconversão - Braga, Rodolpho de Campos (2012)
The biotechnological processes based on the use of microbial enzyme arsenal have great application in the pharmaceutical industry. Microbial models may represent an alternative to using animals in metabolism studies in mammals, providing valuable information on drug metabolism. Montelukast promotes increased lung function and is one of the most prescribed drugs for the treatment of asthma. In 2010, ranked fifth among the best-selling drugs in the world. Considering that in 2012 its patent will expire, it’s necessary the determination of its metabolites, to conduct trials to evaluate the therapeutic efficacy both in the stage of pharmaceutical equivalence and bioequivalence. The aim of this work was the application of bioconversion for the production of human metabolites of montelukast using filamentous fungi as microbial model of mammalian metabolism. Twenty-five microorganisms strains were examined for their ability to transform the antiasthmatic drug montelukast to the phase I metabolites that are found in humans. Metabolomic fingerprinting was used to select the strains that can mimic human metabolism of montelukast. Biostatistical methods were applied to classify the twenty-five strains of microorganisms regarding the type of reaction and products formed. We developed analytical separation strategies and purification of the metabolites using preparative high-performance liquid chromatography (HPLC). Cunninghamella elegans ATCC 36112 and Beauveria bassiana IP98 produced the major variety and quantity of metabolites and were selected to scale up the preparation of the metabolites of montelukast. Seven oxidation metabolites were identified using LC-MS and 1 H and 13C-NMR spectroscopy. The metabolite carboxylic acid (M4) was the major product being converted by both mammalian and microbial systems. Other metabolites were identified as diastereomeric sulfoxides (M2a and M2b), 11-hydroxy (diastereomers of a benzylic alcohol, M5a and M5b), and 3-hydroxy (diastereomers of a methyl alcohol, M6a and M6b). Of the twenty-five strains examined, seventeen transformed montelukast to the main human metabolite carboxylic acid (M4), and the majority also produced the diastereomeric methylhydroxylated metabolites (M6a and M6b). The results support the potential of using the fungus Cunninghamella sp., which can transform a broad range of xenobiotic compounds in an analogous fashion to mammals. The up scaling of the biotransformation may also have potential as a method of generating the metabolites as analytical standards.